Idiopathic Pulmonary Fibrosis: An Update on Pathogenesis - Mei, Qianru; Liu, Zhe; Zuo, He; Yang, Zhenhua; Qu, Jing (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, lethal fibrotic lung disease that occurs primarily in middle-aged and elderly adults. It is a major cause of morbidity and mortality. With an increase in life expectancy, the economic burden of IPF is expected to continuously rise in the near future. Although the exact pathophysiological mechanisms underlying IPF remain not known. Significant progress has been made in our understanding of the pathogenesis of this devastating disease in last decade. The current paradigm assumes that IPF results from sustained or repetitive lung epithelial injury and subsequent activation of fibroblasts and myofibroblast differentiation. Persistent myofibroblast phenotype contributes to excessive deposition of the extracellular matrix (ECM) and aberrant lung repair, leading to tissue scar formation, distortion of the alveolar structure, and irreversible loss of lung function. Treatments of patients with IPF by pirfenidone and nintedanib have shown significant reduction of lung function decline and slowing of disease progression in patients with IPF. However, these drugs do not cure the disease. In this review, we discuss recent advances on the pathogenesis of IPF and highlight the development of novel therapeutic strategies against the disease.